Comparison of volume-controlled ventilation and pressure-limited ventilation in laparoscopic appendicectomy - a randomized controlled clinical trial - Ilamparithi Jayaraman,; Gokul R,; Arulanandam R,; Nirmaladevi S, (Asian Journal of Medical Sciences, 2024)
Background: Laparoscopic appendicectomy is a widely performed surgery globally, offering notable benefits such as reduced postoperative pain, quicker mobility, and shorter hospital stays. Aims and Objectives: The study aimed to assess the changes in respiratory mechanics and compare the outcomes of volume-controlled and pressure-limited ventilation (PLV) in patients undergoing laparoscopic appendectomy. Materials and Methods: This randomized, prospective, single-blinded control study was conducted at K.A.P.V. Government Medical College, Tiruchirapalli, on 60 ASA I and II patients scheduled to undergo laparoscopic appendicectomy under general anesthesia. The patients were randomly divided into two groups (volume-controlled ventilation [VCV] group and the PLV group) of 30 patients. A patient’s history includes age, sex, history of diabetes, hypertension, or any cardiovascular disease, respiratory tract infection, wheezing or chronic chest infections, seizures, neuromuscular disease or weakness, etc. Results: There was no significant difference in gender, age, or body mass index between groups. There is no significant difference in the mean arterial pressure or ETCO2 between groups at various intervals. There was a significant difference in the mean heart rate between the VCV and the PLV groups at 5 and 20 min after induction. There was a significant difference in the peak airway pressure, dynamic compliance, and airway resistance between the VCV group and the PLV group at 10 min after induction (T1), 5 min after pneumoperitoneum (T2), 10 min after pneumoperitoneum (T3), and immediately after Trendelenburg position (T4). Conclusion: The airway resistance and peak airway pressure do not increase, and the dynamic compliance was improved in the PLV during laparoscopic appendicectomy.